2020
DOI: 10.1039/d0md00062k
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy for human schistosomiasis: how far have we come? What's new? Where do we go from here?

Abstract: After a century since the first antimonial-based drugs were introduced to treat the disease, anti-schistosomiasis drug development is again at a bottleneck with only one drug, praziquantel, available for treatment purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 167 publications
0
16
0
Order By: Relevance
“…Praziquantel (PZQ) is an anthelmintic drug widely used in developing countries to treat schistosomiasis, a neglected tropical disease caused by parasitic blood flukes of the Schistosoma genus. 1 Approximately 800 million people are at risk of schistosomiasis and around 250 million are infected, with a high prevalence in the pediatric population. 2 The fluke infection causes chronic immunogenic inflammatory, granulomatous, and fibrotic reactions, accompanied with several functional morbidities that impair normal physiological functioning and growth of an infected child.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Praziquantel (PZQ) is an anthelmintic drug widely used in developing countries to treat schistosomiasis, a neglected tropical disease caused by parasitic blood flukes of the Schistosoma genus. 1 Approximately 800 million people are at risk of schistosomiasis and around 250 million are infected, with a high prevalence in the pediatric population. 2 The fluke infection causes chronic immunogenic inflammatory, granulomatous, and fibrotic reactions, accompanied with several functional morbidities that impair normal physiological functioning and growth of an infected child.…”
Section: Introductionmentioning
confidence: 99%
“… 2 PZQ is included in the World Health Organization List of Essential Medicines for treatments of adults and children as it has good efficiency, a favorable safety profile, and low production costs. 1 …”
Section: Introductionmentioning
confidence: 99%
“…This paper documents the discovery of a potent series of anti-schistosomiasis compounds with excellent prospects for achieving a single dose cure in humans that stand out from those reported in a recent extensive review of the field [17] and series reported since that review [29][30][31]. The weakly potent original hits have been optimised to compounds with approximately three orders of magnitude better in vitro potency.…”
Section: Discussionmentioning
confidence: 99%
“…These include development and application of whole organism screens for compound testing [14], target-based drug discovery [15] and identification of putative molecular targets by analysis of the annotated schistosome genome sequences [16]. A recent comprehensive review of compounds with schistosomicidal activity [17] demonstrates the relative lack of promising series in the area.…”
Section: Introductionmentioning
confidence: 99%
“…A reliable diagnostic method is microscopic detection of eggs in urine, feces, or tissue biopsy together with the detection of specific antibodies, e.g., by ELISA; less frequently, detection of parasitic DNA and RNA by PCR is done [4,5]. Effective peroral medication with praziquantel (PZQ) and oxamniquine (OXA) is available; the mechanism of their action is not known in detail [6]. Human infection occurs mainly after exposure in natural freshwater res Acute and chronic schistosomiasis may be recognized.…”
Section: Introduction 1genus Schistosomamentioning
confidence: 99%